Shear bond strength of orthodontic brackets on enamel surface conditioned by biolase er YSGG laser - Ataee, Kiarash Mehdipoor; Erezo, Earl James; Medina, Vicente III, O.
Introduction. The objectives of this study were to: 1) compare the shear bond strength (SBS) of brackets bonded to enamel, conditioned by Biolase Er:YSGG Laser and to acid-etched enamel; 2) compare the etching patterns on enamel produced by Biolase Er:YSGG laser conditioning and acid etchant, 3) to evaluate the differences in Adhesive Remnant Index between the laser conditioned and acid-etched groups.
Methods. Twenty four bovine lower incisors were randomly assigned to the acid-etched group (n=12). The enamel in the laser conditioned group were irradiated with Er:YSGG (Waterlase, Biolase Europe GmbH, Floss, Germany) with pulse duration of 140m, a pulse repetition rate of 20Hz. It operated at a wavelength of 2780 nm with power setting of 1.5W. An adhesive (Transbond XT, 3M Unitek, USA) was used to bond the stainless steel brackets. The SBS was determined using a universal testing machine (SHIMADZU Autograph, AGS-X, Shimadzu, Japan) at a crosshead speed of 0.5mm/min. A representative specimen from each group was examined using the scanning electron microscope (JEOL, 5300, Jeol, Japan) to compare the etching patterns. The Adhesive Remnant Index (ARI) scores were determined using the magnified digital pictures of the area where the brackets debonded.
Results. The mean SBS of the laser conditioned group was 13.58 +/- 6.1 MPa and the acid-etched group was 23.50 +/- 7.1 MPa. The t-test produced a P-value of .001 indicating that the mean SBS of the acid-etched group is significantly higher than the mean SBS of the laser conditioned group. Although the shear bond strength of the laser conditioned group was less than that of the acid-etched group, the value was still higher than the clinically acceptable SBS, which is the minimum of 6-8 MPa (Reynolds IR et al 1975). SEM evaluation of laser conditioned group and the acid-etched group both showed a Type III etching pattern. The surface appeared rough with irregularities inconsistent with Type I or II etching patterns. The acid-etched surface revealed deep and shallow canals with various widths scattered all around in a bizarre manner. Laser conditioned enamel also revealed an inconsistent pattern of etching with serrated crater shaped areas that ran in different angles. The acid-etched specimens mostly debonded at the adhesive-bracket interface while the laser conditioned specimens commonly showed debonding at the adhesive-enamel interface.
Conclusion. 1) Laser conditioning of enamel surfaces by the Biolase Er:YSGG laser produced a mean SBS value of 13.58 MPa; higher than the clinically acceptable bond strength. 2) The SEM picture of the laser conditioned and acid-etched enamel surfaces showed an irregular pattern of etching consistent Type III etching pattern. In the laser conditioned group, debonding was generally at the enamel-adhesive interface while in acid-etched group debonding was mostly at the adhesive-bracket interface.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Orthodontics; Shear bond strength